ANALISIS KADAR BIOETANOL HASIL FERMENTASI DARI NIRA NIPAH (Nypa fruticans wurmb) ASAL PAPUA - Sefnat Sopater Runtuboi; Maria Ludya Pulung; Evelina Somar (FMIPA Universitas Papua, 2019)
This study aims to analyze the ethanol content in fermented palm juice.This research includes the preparation of raw materials, fermentation, distillation and distillation products analyzed by gas chromatography method. Fermentation is carried out for 2, 5, 7 days, the highest level of bioethanol produced is then selected for distillation. Levels the highest fermentation process is on the 5th day with a level of 18%. Got results the final distillation is 117 mL with a level of 94% of the initial volume of 4.2 L fermentation based on measurements using an alcoholmeter while the analysis by gas chromatography yielded 93.9% levels. The density of bioethanol is 0.8232 gr / mL. The results of the retention time measurement show the sample has a retention time which is almost the same as standard ethanol, namely 3,761 standard ethanol samples 3,764. From retention time data can be concluded that the sample is ethanol. Ethanol content in sample based on analysis by gas chromatography is 93.9%